DEVELOPMENT AND FORMALIZATION STRATEGY OF LABOR MARKET IN KAZAKHSTAN UNDER THE CONDITIONS OF DIGITALIZATION - Tatibekov, B.L. (Academic Journal of Physical and Chemical Sciences, 2018)
The paper is aimed at developing the main trends of labor market and employment development under the digitalization of Kazakhstan economy. A variety of methods, combined by a systematic approach to the study of the labor market and the employment of human resources were applied for the research. Based on the historical analysis, the article analyzes the features of the integration of the Kazakhstan labor market into the international markets. An important point of this analysis is that the existing trends in the development of international labor migration are revealed through the prism of the laws of Gravity. Based on the features of the digitalization development, the work substantiates the need to use new tools for employment registering, in particular, the introduction of biometric registration of migrant workers. In addition, the article pays special attention to the development of outsourcing and a globally-individualized labor market. The author has developed some strategic trends for development and formalization of the labor market in Kazakhstan under digitalization process. Recommendations on the formation of international integrated databases on labor migration and the development of the Concept of human resources employment in Kazakhstan are proposed.